Oscillation of Second-Order Sublinear Impulsive Differential Equations - A. Zafer (Abstract and Applied Analysis)
Oscillation criteria obtained by Kusano and Onose (1973) and by Belohorec (1969) are extended to second-order sublinear impulsive differential equations of Emden-Fowler type: x″(t)+p(t)|x(τ(t))|α-1x(τ(t))=0, t≠θk; Δx'(t)|t=θk+qk|x(τ(θk))|α-1x(τ(θk))=0; Δx(t)|t=θk=0,   (0<α<1) by considering the cases τ(t)≤t and τ(t)=t, respectively. Examples are inserted to show how impulsive perturbations greatly affect the oscillation behavior of the solutions.